THE INFLUENCE OF SCREEN-BASED TEXT TOWARDSTUDENTS’ READING COMPREHENSION IN TOEFL PREDICTION TEST - Pretti Ristra; Doris Sukma; Agnes Arum Budiana (International ABEC, 2022)
Students’ reading comprehension quality is highly influenced by some salient features such as method of instruction, media/technology used, class size, students’ prior ability, teaching materials, etc. This experimental study explores the influence of technology in teaching reading through the use of computer screen as opposed to conventional mean, i.e., the use of textbook in teaching reading comprehension for TOEFL test. While some argues that paper-based reading text is still relevant today, the use of technology like screen-based text is believed to help students to understand and comprehend reading text better due to some important reasons. The design of the study is experimental research which includes 117 students from some departments in Riau University. There are two groups of students involved in this study namely control (54 students) and experimental (63 students) group which receive different treatment in the process of teaching and learning within 7 meetings. Based on the result of the study, the students’ reading comprehension score in TOEFL after they were given the treatment shows that 36.320 mean score for the control group and 40.310 mean score for the experimental group. The value of Sig. (2-tailed) is 0.001 and it is smaller than the value of Alpha 0.05. Thus, it implies that H0 is rejected, and Ha is accepted. In other words, it can be said that there is a significance difference between students’ reading comprehension in experimental and control groups. Based on the statistical analysis of the data, it is found that students who are treated with screen-based text have better reading comprehension than those who used paper-based text. It can be concluded that screen-based text is effective enough to improve students’ reading comprehension in TOEFL prediction test.